Rapid decline in antioxidant activity of freshly prepared strawberry (Fragaria x ananassa) juice during short-term cold storage: a DPPH study - Henny Erina Saurmauli Ompusunggu; Febrina D. N. Zebua; Ana Stela Yofani Brahmana (AcTion: Aceh Nutrition Journal, 2026)
Strawberries (Fragaria × ananassa) are rich in phenolic antioxidants, particularly anthocyanins, which degrade during processing and storage. However, the rate of antioxidant loss in freshly prepared strawberry juice during the first few days of typical home refrigeration—the exact period a consumer would drink it—remains insufficiently quantified. This study evaluated the antioxidant activity of freshly prepared strawberry juice stored at 4°C (chiller) for 0, 1, 3, and 5 days using the DPPH (1,1-diphenyl-2-picrylhydrazyl) radical scavenging assay. Sample concentrations of 100–500 ppm (w/v) were tested in triplicates. The presence of flavonoids was qualitatively confirmed using the Shinoda test. IC50 values were derived from the linear regression of the percentage of inhibition versus concentration. Fresh juice exhibited the highest antioxidant capacity (IC50 = 140 ppm; moderate activity). After only one day of chiller storage, the IC50 increased substantially to 225 ppm, a ~61% increase, indicating a significant loss of potency. Further increases to 257 ppm (day 3) and 272 ppm (day 5) placed the samples in the weak activity category (IC50 > 150 ppm per Yuslianti, 2018). An anomalous decrease in the% inhibition at 500 ppm in the fresh sample was noted and discussed as a likely measurement artifact. In conclusion, these findings demonstrate that strawberry juice loses a substantial proportion of its antioxidant potency within 24 h of preparation. Strawberry juice should ideally be consumed within one day of preparation for meaningful antioxidant benefit.